2023
DOI: 10.1111/ggi.14621
|View full text |Cite
|
Sign up to set email alerts
|

Association of carnitine insufficiency with sarcopenia and dynapenia in patients with heart failure

Abstract: Aim L‐carnitine transports fatty acids into mitochondria and contributes to energy metabolism in skeletal muscles. However, the association between carnitine insufficiency and skeletal muscle weakness, namely sarcopenia and dynapenia, in patients with heart failure (HF) remains unclear. Methods In total, 124 patients with HF were enrolled in this study. Carnitine insufficiency was indicated by a decrease in serum free carnitine (FC) levels of less than 36 μmol/L or an elevated serum acylcarnitine (AC) to free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Serum AC might contribute to the worsening of HF through the promotion of arrhythmias, insulin resistance, adverse remodeling, and reduced energy production [19] . Previous studies have reported an association between the AC/FC and cardiac events in patients with HF, suggesting that the AC/FC may increase in patients with HF due to mitochondrial dysfunction, which is associated with impaired energy metabolism [13] , [14] . Yoshihisa et al [13] reported that patients with HF with an AC/FC ≥ 0.27 had the highest rate of cardiac events, including cardiac death and HF progression, and the AC/FC was a predictor of cardiac events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum AC might contribute to the worsening of HF through the promotion of arrhythmias, insulin resistance, adverse remodeling, and reduced energy production [19] . Previous studies have reported an association between the AC/FC and cardiac events in patients with HF, suggesting that the AC/FC may increase in patients with HF due to mitochondrial dysfunction, which is associated with impaired energy metabolism [13] , [14] . Yoshihisa et al [13] reported that patients with HF with an AC/FC ≥ 0.27 had the highest rate of cardiac events, including cardiac death and HF progression, and the AC/FC was a predictor of cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshihisa et al [13] reported that patients with HF with an AC/FC ≥ 0.27 had the highest rate of cardiac events, including cardiac death and HF progression, and the AC/FC was a predictor of cardiac events. Also, Kinugasa et al [14] found that in patients with HF, sarcopenia was associated with older age (>77 years) and a high AC/FC (>0.31) in patients aged 64–76 years, suggesting that carnitine deficiency is a potential therapeutic target against sarcopenia in patients with HF. The present study showed that the serum AC concentration, but not the AC/FC, is associated with echocardiographic findings and BNP in male patients undergoing cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation